Sri Guru Gobind Singh Ji And Guru Ki Kashi, Damdama Sahib - Vijay Shankar Prasad (Elementary Education Online, 2023)
This research paper presents an informative, authentic and comprehensive document for the promotion of the place Talwandi Sabo as a centre of education, scholarship, learning and research as was the sacred blessings originally by the tenth and last Guru of the Sikh, Sri Guru Gobind Singh Ji. He had started his mission to obtain an honour and standard for this place like that of Kashi, the most reputed centre of education and learning in India. He had chosen this place, Damdama Sahib for his learning pursuits. He had congregated the galaxy of scholars here who had acquired education and knowledge of almost all the available subjects of his time and thus named the place as Guru Ki Kashi. The most remarkable fact about this place is that the final version of Sri Guru Granth Sahib, which is accepted and respected all over the world, was compiled by Guru Ji here only in 1706 during his stay for about 9 months. His vision was to make a parallel Kashi here.